Intensification of phenolic acids extraction from Aleppo oak via probe type sonication method: Kinetic, antioxidant and cost evaluation - Nuramira Fateha, Sukor; Rohayu, Jusoh; Nur Syahirah, Kamarudin (Elsevier Ltd, 2021)
This work aimed to evaluate the optimum conditions for efficient extraction of phenolic acids, namely gallic acid (GA) and tannic acid (TA) from Aleppo oak by ultrasonic-probe assisted extraction (UPAE) method. Furthermore, an extensive study on kinetic, antioxidant activity and cost evaluation aspects in comparison with classical hydro-distillation extraction (CHDE) method was also examined. Sonication demonstrated a superior effect on the extraction of target compounds in which the UPAE method was seven times more efficient compared to the classical hydro-distillation extraction (CHDE) method. Result revealed that under optimized optimum condition of 40% duty cycle and 70 °C extraction temperature, GA and TA were yielded at 870.90 ± 0.03 mg GAE/g and 3157.97 ± 0.05 mg TAE/g, respectively. Kinetic analysis affirmed the extraction rate as controlling factor in extracting phenolic acids. Strong antioxidant activity was observed at a IC50, 26.57 ± 0.03 μg/mL. Besides, the cost assessment study indicates that the extraction process requires US$ 0.25 and US$ 0.06 per mg/g extracts produced for CHDE and UPAE, respectively. Notably, findings revealed that UPAE method is four-fold more cost-effective compared to the CHDE method, providing a new direction for extracting active compounds from complex plants.